Health Business Sustainability in the Era of Globalization: a Reflection Analysis of Readiness and Challenges in Indonesia and the World - Zaenal Muttaqin; Deasy Silvya Sari (PT Publikasiku Academic Solution, 2024)
Every human being in any part of the world needs continuous health, both in normal conditions and in pandemic conditions. Health is one of the human capital that is indispensable in supporting economic development. This is because health is a prerequisite for increased productivity. Along with the development of today's era, the development of digitalization has grown rapidly. This has an impact on the sustainable health business at this time. This study aims to describe various health business challenges and opportunities that will be faced in the era of industrial globalization. This research uses a qualitative approach with a literature study method, which collects various information answering the formulation of research problems through various sources such as books and journals. The results of this study show that Globalization and climate change can be a significant influence on an economy, as happened in Indonesia and other countries. Globalization can affect policies set in the country specifically in other fields. The health industry makes all healthcare industry providers compete with each other to compete for competitive advantage amid potential health markets